Mass Transfer over a Film-Cooled Turbine Blade - Ping-Hei Chen; Jr-Ming Miao (International Journal of Rotating Machinery, 1996)
A naphthalene sublimation technique was employed to study the mass transfer distributions over a turbine blade surface with secondary flows ejected in the spanwise direction through three rows of equally-spaced injection holes located in the leading edge region. The mass transfer measurements were conducted in a range of blowing ratios from 0.6 to 1.2 at two different mainstream turbulence levels (0.4% and 6.0%) while keeping the exit Reynolds number, Re⁡2, at a constant value of 397,000.